General practitioners’ beliefs and attitudes about how to respond to death and bereavement: qualitative study - Saunderson, Eric M (BMJ Group, 1999)
OBJECTIVES: To investigate the perceptions of general practitioners when they are notified or hear of a death or bereavement in their practice; to explore doctors’ accounts of their relationships with their patients in the context of bereavement; and to explore the concerns of general practitioners in managing themselves and bereaved patients. DESIGN: Semistructured interviews followed by qualitative content analysis. SETTING: London borough of Redbridge. PARTICIPANTS: 25 general practitioners. RESULTS: Almost all the doctors had felt guilty about issues relating to the death of patients. These feelings were based on their expectations of not making mistakes and diagnostic precision. They described a culture gap existing between hospital and general practice and a need to develop new models and methods to explain and manage the causes of illness presented to them. In the absence of useful teaching on bereavement, many devised strategies which relied more on their personal experiences. General practitioners used various methods to contact bereaved patients, especially if they had been involved in the terminal care or if the death was particularly shocking. The doctor was also bereaved by the death of well known patients and sometimes needed to grieve and express emotion. CONCLUSION: General practitioners may need support and learning methods to manage their own and their patients’ bereavement.